UPAYA FRONT DESK AGENT DALAM MENANGANI KELUHAN DAN PERMINTAAN TAMU DI BATAM MARRIOTT HARBOUR BAY - Fransiska Lauren; Zahara Fatimah (Jurnal Manajemen Perhotelan dan Pariwisata, 2025)
In Batam, tourism growth has driven the development of international star-rated hotels such as the Batam Marriott Hotel Harbour Bay. However, this hotel faces numerous guest complaints regarding room comfort, service quality, cleanliness, and staff professionalism. This study aims to evaluate the role of Front desk Agents (FDAs) in handling guest complaints and requests at the Batam Marriott Hotel Harbour Bay. The method used was a descriptive qualitative approach through interviews and observations of the FDAs. Data were collected through probing techniques at check-in and monitoring guest feedback. Data analysis was conducted to identify emerging complaint patterns and the FDA's role in addressing them. The results indicate that FDAs play a crucial role in identifying guest needs through guest history recording and probing techniques at check-in. The most frequent complaints related to the accuracy of room information, service respone times, and interdepartmental coordination. Discussions indicate that ongoing training for hotel staff and more proactive communication between departments are crucial to improving service quality.